KOMUNIKASI DAKWAH EFEKTIF DALAM PERSPEKTIF ALQURAN - Markarma, Andi (Hunafa: Jurnal Studia Islamika, 2014)
In the Koran perspective, the effective dawah communicationÂ  (qaulan balÄ«ghan) is highly recommended. The abilityÂ  or a preacher to communicate effectively can affect the relative truth of thought ofÂ  the audience or mustamiâ (listeners). The Koran insists that Islam is a perfect religion and must be socialized and internalized into the minds of its adherents in order to understand and to implement it consistently and cuntinually. The daâI must possess a good mastery of communication, in Arabic, qaulan balÄ«ghan, in order to be able to internalize the teachings of Islam into the minds of its adherents, through which they will behave as true Muslims.Kata Kunci: dakwah, komunikasi, perspektif Alquran ansiï¿½fgaï¿½ï¿½:@ï¿½:mso-fareast-language:EN-US;mso-bidi-language:AR-SA>: Â Â Â Â Â Â  Corak, quasi-Obyektifis Tradisionalis, Obyektifis, quasi Obyektifis Modernis